2012
DOI: 10.1002/jcb.24048
|View full text |Cite
|
Sign up to set email alerts
|

A2a adenosine receptor mediates HepG2 cell apoptosis by downregulating Bcl‐XL expression and upregulating bid expression

Abstract: Extracellular adenosine induced apoptosis in HepG2 cells, a human hepatoma cell line, by tuning apoptosis-mediator gene transcription. The present study aimed at identifying the responsible adenosine receptor and clarifying the signaling pathway underlying adenosine-induced HepG2 cell apoptosis. Adenosine and CGS21680, an A(2a) adenosine receptor agonist, induced HepG2 cell apoptosis, and the effect was inhibited by DMPX, an A(2a) adenosine receptor antagonist, or by knocking-down A(2a) adenosine receptors. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…Adenosine causes cytosolic Ca 2+ overload, ΔΨm loss and caspase-3 activation. Knockdown of GRP78 further aggravates the loss of ΔΨm and adenosine-induced apoptosis, indicating that other apoptotic pathways such as the mitochondrion pathway, may participate in the process [37] and that GRP78 is involved in the regulation of ΔΨm [30,31]; other possibilities include autophagy [38] and other miRNAs, such as miR-30d, miR-181a and miR-199a-5p [39]. …”
Section: Resultsmentioning
confidence: 99%
“…Adenosine causes cytosolic Ca 2+ overload, ΔΨm loss and caspase-3 activation. Knockdown of GRP78 further aggravates the loss of ΔΨm and adenosine-induced apoptosis, indicating that other apoptotic pathways such as the mitochondrion pathway, may participate in the process [37] and that GRP78 is involved in the regulation of ΔΨm [30,31]; other possibilities include autophagy [38] and other miRNAs, such as miR-30d, miR-181a and miR-199a-5p [39]. …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the evidence gathered in the last 20 years clearly speaks against this dogma of A 2A R signaling only or mainly through the cAMP-PKA pathway. In different tissues and cells, A 2A R activation has been shown to recruit and to signal through a variety of transducing pathways such as MAPK, namely ERK1/2 (extracellular signal-regulated kinases), p38 or c-Jun N-terminal kinases, PI-3K (phosphoinositide 3-kinase), protein phosphatases, protein kinase C, Src (acronym for sarcoma) kinases, or peroxisome proliferator-activated receptor, as illustrated by this non-exhaustive list of studies (Gubitz et al 1996;Revan et al 1996;Sexl et al 1997;Palmer and Stiles 1999;Seidel et al 1999;Gardner and Olah 2003;Murphy et al 2003;Boucher et al 2004;Fotheringham et al 2004;Gsandtner et al 2005;Pinto-Duarte et al 2005;Yu et al 2005;Melani et al 2006Melani et al , 2009Sun et al 2006Sun et al , 2010Che et al 2007;De Ponti et al 2007;Fresco et al 2007;Charalambous et al 2008;Tikh et al 2008;Canas et al 2009a,b;Simões et al 2012;Tamura et al 2012;Ahmad et al 2013;Nayeem et al 2013;Wang et al 2014;Zeidan et al 2014;Merighi et al 2015;Piirainen et al 2015;Shang et al 2015;Zhang et al 2015;Mohamed et al 2016).…”
Section: Signaling Mechanisms Underlying a 2a R-mediated Neurodegenermentioning
confidence: 99%
“…In conclusion, there is a substantial gap of knowledge in the signaling mechanisms operated by A 2A R. This precludes any realistic proposal on pathways operated by A 2A R to control neurodegeneration, although, as occurs for the control of proliferation of endothelial cells, it is unlikely that the prototypically assumed cAMP-PKA might be involved. It is hoped that the newly established links between A 2A R and the control of mitochondrial function and apoptosis (Silva et al 2007;Tamura et al 2012;Visentin et al 2013;Huang et al 2015;Tosolini et al 2015), as well as the control of the cytoskeleton (Burgueño et al 2003;Sohail et al 2009;Zeidan et al 2014;Shang et al 2015) may open new opportunities to unravel the mechanisms operated by A 2A R to control neurodegeneration.…”
Section: Different a 2a R-containing Heteromersmentioning
confidence: 99%
“…A growing body of evidence has shown that high concentrations of extracellular adenosine is capable of inducing apoptosis in a variety of cancer cells mainly through intrinsic and/or extrinsic pathways [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]. ADA, an enzyme involved in purine metabolism, catalyzes the hydrolytic deamination of adenosine and 2'-deoxyadenosine to their corresponding hypoxanthine derivatives, inosine and 2'-deoxy-inosine.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine induces apoptosis in CW2 human colonic cancer cells and RCR-1 rat astrocytoma cells via A 1 adenosine receptor [9,10]. Adenosine induces apoptosis in Caco-2 human colonic cancer and HepG2 cells via A 2a adenosine receptor [11,12]. A 3 adenosine receptor mediates apoptosis in human lung cancer cells, hepatocellular carcinoma cells, thyroid cancer cells, breast cancer cells, renal cancer cells, bladder cancer cells, and MPM cells by the diverse independent mechanisms [13,14,15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%